Socio-economic development of agglomeration territories as an object of strategic management - G. A. Borovkova; D. V. Rodnyansky (Управление)
The object of this article is to build forecasts of the development of Kazan, Naberezhnye Chelny and Almetyevsk agglomerations, located in the territory of the Republic of Tatarstan. The agglomerations’ formation has firmly taken place as one of the main strategic goals of our country’s development over the past few years. According to forecasts, almost 80% of GDP growth until 2020 will be provided by agglomerations. In this regard, it is especially important to study the existing agglomerations from the position of the achieved and future level of development. The results of the analysis of these agglomerations’ state over the past decade have presented in the article, on the basis of which the forecasts of the development of these agglomerations in the medium term until 2020 were calculated. The research methodology is the least squares method and the moving average method, comparing the results of which allowed us to make more adequate forecasts. When using each of the methods, also there was carried out the analysis of the forecast’ average relative error. A comparative analysis of the situation and agglomerations’ forecasts showed that Kazan agglomeration can be considered the most developed, because most of the estimated indicators show growth. Naberezhnye Chelny and Almetyevsk agglomerations lag behind Kazan agglomeration especially in demographic indicators. In general, all three studied agglomerations in the formation of their development plans should focus their attention primarily on level of migration, the volume of investment in fixed capital per capita, GDP per capita factors. The conducted analysis allowed to identify the main trends in the development of each agglomeration, as well as to formulate recommendations for the management of these agglomerations development.